Xenopholis undulatus - Soares Tiburcio, Ingrid Carolline (2016)
This species ispreviously known from the Brazilian states of Ceará, Goiás, Maranhão,Mato Grosso do Sul, Minas Gerais, Pará, Paraná, Pernambuco,São Paulo, and Tocantins (Hoge and Federsoni 1975.Mem. Inst. Butantan 38:137-146; Cunha and Nascimento 1993.Bol. Mus. Para. Emílio Goeldi, sér. Zool. 9:1-191; Nogueira 2001.Herpetol. Rev. 32:285-287; França et al. 2008. Copeia 2008:23?38;Loebmann 2009. Herpetol. Rev 40:117; Ribeiro et al. 2011. Herpetol.Rev 42:116) and from Paraguay (Hoge and Federsoni 1975, op.cit.). As in Ribeiro et al. (2011, op. cit.), our record suggests thatthis species inhabits fragments of the Northeast Atlantic Forest.This specimen is the first state record and the second one for theAtlantic Forest in northeastern Brazil. This extends the knowndistribution ca. 240 km SE from Camaragibe, Pernambuco, Brazil(Ribeiro et al. 2011, op. cit.) and approximately 1040 km NNEfrom the type locality (Lagoa Santa, Minas Gerais; Jensen 1900.Vidensk. Medd. Naturhist. Foren. Kjöbenhavn 1899:99-111).